2016
DOI: 10.1111/ajag.12364
|View full text |Cite
|
Sign up to set email alerts
|

Older patients' consultations in an apprenticeship model‐based general practice training program: A cross‐sectional study

Abstract: Our results suggest relatively limited GPR exposure to older patients coupled with less complex consultations than expected. Solutions will need to be carefully constructed not only to increase caseloads, but also to address training and supervision concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Previous ReCEnT analyses suggest GP registrar experiences of interpersonal continuity of care might not be optimal, so regional and rural practice might be valuable in increasing registrars’ in‐training exposure to continuity. Similarly, our previous work has established that registrars have a relative deficit compared to established GPs in experience of older patient care, so our findings showing that registrars practising rurally see a greater proportion of older patients are again valuable in‐training exposure.…”
Section: Discussionsupporting
confidence: 76%
“…Previous ReCEnT analyses suggest GP registrar experiences of interpersonal continuity of care might not be optimal, so regional and rural practice might be valuable in increasing registrars’ in‐training exposure to continuity. Similarly, our previous work has established that registrars have a relative deficit compared to established GPs in experience of older patient care, so our findings showing that registrars practising rurally see a greater proportion of older patients are again valuable in‐training exposure.…”
Section: Discussionsupporting
confidence: 76%
“…This level of registrar engagement has not always been evident in other ReCEnT analyses. Analyses of continuity of care in registrars’ consultations, and of consultations with older patients and patients with chronic disease, have suggested limited therapeutic engagement in these areas . This analysis’ finding of a non‐significant trend for older patient age being associated with less dietitian/nutritionist referral than middle‐aged patients (despite increasing diet‐related morbidity with age) may reflect a general lack of engagement with the management of older patients, being evident also in diet‐related aspects of health.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the breadth of responsibility, several studies have identified GPs’ current dementia training as inadequate in preparing them for the timely diagnosis and ongoing management of dementia 5 11 17–19. While GP registrars are exposed to a wide range of patients in their training,20 they have limited exposure to those over 65 years of age and those they do see tend to have less complex medical conditions than those seen by more experienced GPs 21 22. Importantly, poor knowledge of dementia among GPs has been identified as one factor contributing to low rates of dementia diagnosis, delayed diagnoses and poor management outcomes 11.…”
Section: Introductionmentioning
confidence: 99%